Optimization of pectinolytic hydrolysis in Caatinga passion fruit wine must with commercial pectinase, according to the central composite rotatable design approach (Research, Society and Development, 2022)
The Passiflora cincinnata Mast. has high flavor and potential for wine and other alcoholic beverages production. However, for wine production, the presence of pectin becomes undesirable, as it influences the efficiency of the fermentation process and the clarity of the final product. The objective of this study was to optimize the pectin hydrolysis process in Caatinga passion fruit must for wine production with pectinolytic enzymes, using a Central Composite Rotatable Design (CCRD). The 2³ factorial CCRD, E01 to E17 assays, was applied with six axial tests and three replications in the central point. Caatinga passion fruit must was obtained with pulp and distilled water (40:60 proporcion). Commercial enzyme with high concentration of pectinase was tested. Concentration of enzyme (0.014-0.056 g L-1), working temperature (43-57°C) and reaction time (12-139min) were the independent variables in the optimization process; and the soluble pectin content (mg 100g-1) corresponded to a process-dependent variable. Prior to the beginning of the assays, in order to provide the optimum working pH range for the pectinase, correction of the must pH to 3.9. The initial Caatinga passion fruit wine must had 24.06 mg 100g-1 of soluble pectin in its composition. After the optimization using CCRD, the treatments presented pectin contents ranging from 6.81 (E16: 0.014g L-1/50°C/75min) to 0.00 mg 100 g-1 (E05: 0.05 g L-1/45°C/ 30min and E06: 0.05 g L-1/45°C/120min). According to the results, to a satisfactory process of pectin hydrolysis in Caatinga passion fruit wine must be added 0.05 g L-1 of pectinase at 45°C for 30min.